The Role of Interactive Walls in Supporting Reading Skills among Inclusive Education Students: School Principals’ Perspectives - Sumaia Ali Al Soud; Sita Juhaysh Al-Shar’ah (Bumi Publikasi Nusantara, 2026)
This study examined school principals’ perceptions of the role of interactive walls in supporting reading skills among inclusive education students in Jordan. A descriptive survey design was used with 50 principals selected through purposive sampling. Data were collected using a 32-item questionnaire covering fluency, originality, flexibility, and elaboration. The results showed that principals perceived interactive walls as highly supportive of students’ reading skills overall, with fluency and flexibility receiving the highest ratings and elaboration receiving a moderate rating. Statistically significant differences were found according to gender, academic qualification, and years of experience. The study recommends integrating interactive walls with structured reading instruction to support inclusive and engaging literacy practices.